Non-destructive test of watermark materials quality for art pottery using x-ray digital radiography. (June 2020) - Dewi, N R; Listiaji, P; Marwoto, P; Iswari, R S
Abstract: In this study, the quality of watermark materials for art pottery were tested using x-ray digital radiography. The embedded watermarks in art pottery were chosen from 3 materials namely wood, and polylactic acid (PLA), and acrylic. Watermarked potteries quality testing were carried out during the making process, namely before and after being burned. Watermarked potteries were tested with 60 kV tube voltage regulation, 16 mA strong current, and 0.16 s exposure time. The radiographic image results obtained were then analyzed using ImageJ software. There are 3 stages of testing, namely visual analysis, image line profile analysis, and linear attenuation coefficients analysis. The results of visual analysis show that there were no crack in the watermarks so that planting the watermark did not damage the pottery. The graph of image line profile analysis results shows that the watermark made from wood was most clearly seen on the radiographic image. The attenuation coefficient value in the watermarked part does not change before and after the burning process while the attenuation coefficient value of the pottery had increased due to the shrinking process of the pottery. Wood has the largest attenuation coefficient value difference with pottery, so making it suitable as a watermark material for art pottery.